2021
DOI: 10.1128/msphere.00031-21
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Deficiency, Caused by Malnutrition, Makes You Susceptible to SARS-CoV-2 Infection but Could Offer Protection from Severe COVID-19

Abstract: In much of the developing world, severe malnutrition is the most prevalent cause of immunodeficiency and affects up to 50% of the population in some impoverished communities. As yet, we do not know how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) will behave in populations with immunodeficiency caused by malnourishment. Interestingly, researchers are now speculating that, in some instances, a defective cellular immune system could paradoxically be a protective factor against severe disease in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Resistance to insulin and hyperglycemia impair immune cell function directly or indirectly via oxidants generation and glycation products. On the other hand, malnutrition and in particular protein energy malnutrition (PEM) has been linked to immunosuppressive phenotype due to decreased levels of adipokine and leptin [12]. Leptin has been shown to shift the immune response from an anti-inflammatory profile to a more pro-inflammatory one validating the immunosuppressive profile seen in leptin-deficient malnourished patients.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to insulin and hyperglycemia impair immune cell function directly or indirectly via oxidants generation and glycation products. On the other hand, malnutrition and in particular protein energy malnutrition (PEM) has been linked to immunosuppressive phenotype due to decreased levels of adipokine and leptin [12]. Leptin has been shown to shift the immune response from an anti-inflammatory profile to a more pro-inflammatory one validating the immunosuppressive profile seen in leptin-deficient malnourished patients.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin modulates both innate and adaptive immune responses in monocytes/macrophages ( Curat et al, 2004 ), neutrophils, eosinophils, effector, and regulatory T lymphocytes ( Bruno et al, 2005b ; Conus et al, 2005 ; Lourenço et al, 2016 ). Furthermore, a large amount of literature reports an important association between leptin and inflammation ( Naylor and Petri, 2016 ; Becerril et al, 2018 ; Ziegler et al, 2019 ; Schoeman and Fielding, 2021 ).…”
Section: Leptin At a Glancementioning
confidence: 99%
“…Conversely, other studies have suggested that leptin production is upregulated by TNF-α and IL-1β (41)(42)(43), possibly forming a pro-inflammatory feedback loop. The administration of inflammatory stimuli, such as lipopolysaccharide, enhances leptin production (44,45), whereas leptin deficiency likely results in an immunosuppressive phenotype characterized by reduced levels of inflammatory cytokines (46,47). Furthermore, animal studies have suggested that maternal systemic inflammation, induced by factors such as a high-fat diet, causes disrupted leptin signaling and affects neurodevelopment in children (48)(49)(50).…”
Section: Introductionmentioning
confidence: 99%